Anionic sites in the glomerular basement membrane. In vivo and in vitro localization to the laminae rarae by cationic probes (The Rockefeller University Press, 1979)
Cationized ferritin (CF) of narrow pI range (7.3-7.5) and the basic dye ruthenium red (RR) have been used as cationic probes to partially characterize anionic sites previously demonstrated in the glomerular basement membrane (GBM). When CF was given i.v. to normal rats and the left kidney was fixed by perfusion 15 min thereafter, clusters of CF molecules were found throughout the lamina rara interna (LRI), lamina rara externa (LRE), and mesangial matrix distributed at regular (approximately 60 nm) intervals. When kidneys were perfused with aldehyde fixative containing RR, small (20 nm) RR-stained particles were seen in the same locations distributed with the same 60 nm repeating pattern, forming a quasiregular, lattice-like arrangement. Fine (approximately 3 nm) filaments connected the sites and extended between them and the membranes of adjoining endothelial and epithelial cells. When CF was given i.v. followed by perfusion with RR in situ, both probes localized to the same sites. CF remained firmly bound after prolonged perfusion with 0.1-0.2 M KCl or NaCl. It was displaced by perfusion with buffers of high ionic strength (0.4-0.5 M KCl) or pH (less than 3.0 or greater than 10.0). CF also bound (clustered at approximately 60 nm intervals) to isolated GBM's, and binding was lost when such isolated GBM's were treated with buffers of high ionic strength or pH. These experiments demonstrate the existence of a quasi- regular, lattice-like network of anionic sites in the LRI and LRE and the mesangial matrix. The sites are demonstrable in vivo (by CF binding), in fixed kidneys (by RR staining), and in isolated GBM's (by CF binding). The results obtained with CF show that the binding of CF (and probably also RR) to the laminae rarae is electrostatic in nature since it is displaced by treatment with buffers of high ionic strength or pH. With RR the sites resemble in morphology and staining properties the proteoglycan particles found in connective tissue matrices and in association with basement membranes in several other locations.